PENYALAHGUNAAN PENGUNGKAPAN INFORMASI TANGGUNG JAWAB SOSIAL PERUSAHAAN UNTUK MEMANAJEMEN LABA PERUSAHAAN : Studi Empiris terhadap Perusahaan Go Public Sektor Mining Tahun 2017-2019 - Angestie, Aneta Yoshinta; Ghozali, Imam (Diponegoro Journal of Accounting, 2021)
The implementation of the company's operational activities in fact requires a responsibility towards the obligation to maintain the environment or Corporate Social Responsibility (CSR). In practice, sometimes the company commits a violation of reporting and recording so that the company's management can be manipulated. Earnings management is used as the dependent variable which is measured by using discretionary accruals. This study requires control variables which include: profitability ratios (ROA), solvency ratios (DAR), and leverage ratios. The company standards used are mining companies for 2017, 2018, and 2019, which provide complete financial reporting and sustainability reports. This study found that good social responsibility disclosure practices tend to motivate management behavior to perform earnings management in mining companies. Specifically, the publication of social responsibility activities creates trust and adds value to the company, so that by gaining the trust of stakeholders, management can more freely practice earnings management.